2022
DOI: 10.1257/aer.20201063
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Implications of COVID-19: Can Negative Supply Shocks Cause Demand Shortages?

Abstract: Motivated by the effects of the COVID-19 pandemic, we present a theory of Keynesian supply shocks: shocks that reduce potential output in a sector of the economy, but that, by reducing demand in other sectors, ultimately push aggregate activity below potential. A Keynesian supply shock is more likely when the elasticity of substitution between sectors is relatively low, the intertemporal elasticity of substitution is relatively high, and markets are incomplete. Fiscal policy can display a smaller multiplier, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(137 citation statements)
references
References 40 publications
2
80
0
4
Order By: Relevance
“…Another strand of papers develops multi-sector models and highlights the importance of sector linkages and spillover. Guerrieri et al. (2022) show in a stylised two-sector model how incomplete markets and complementarity in demand for sectoral output give rise to ‘Keynesian’ supply shocks, where a negative supply shock in the restricted sector (e.g.…”
Section: Related Literaturementioning
confidence: 99%
“…Another strand of papers develops multi-sector models and highlights the importance of sector linkages and spillover. Guerrieri et al. (2022) show in a stylised two-sector model how incomplete markets and complementarity in demand for sectoral output give rise to ‘Keynesian’ supply shocks, where a negative supply shock in the restricted sector (e.g.…”
Section: Related Literaturementioning
confidence: 99%
“…However, monetary policy, especially if not impeded by the zero‐lower bound, can generate notable results, including preventing firm exits and incentivizing labor retention. Guerrieri et al ( 2022 ) confirmed that lockdown of contact‐intensive sectors coupled with the provision of full insurance payments to affected workers is the optimal policy.…”
Section: Summary Of Relevant Literaturementioning
confidence: 98%
“…Guerrieri et al ( 2022 ) argued that Keynesian supply shocks 7 could be generated in a multiple‐sector, incomplete‐markets economy under certain conditions. For instance, firm exit and loss of jobs can escalate the initial effects, thereby intensifying the recession.…”
Section: Summary Of Relevant Literaturementioning
confidence: 99%
“…This was followed in 2022 by the war in Ukraine and prolonged supply chain bottlenecks with skyrocketing energy prices and soaring inflation. Initially, the COVID-19 crisis appeared to be both supply and demand shocks, but the observed demand effects were mainly due to restrictions-not due to the willingness or ability to consume (Guerrieri et al 2022). The central banks acted decisively and provided the market with ample liquidity, possibly contributing to the historically high asset price valuations (Borio 2020;Cantú et al 2021;Echarte Fernández et al 2021).…”
Section: Introductionmentioning
confidence: 99%